FAKTOR- FAKTOR YANG MEMPENGARUHI BIAYA MODAL EKUITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2021 - Sinka Septiyani; Tabrani; Budi Raharjo, Teguh (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to examine the effect of information asymmetry, earnings quality, firm size, and voluntary disclosure with the Cost of Equity Capital in Food and Beverage Companies listed on the Indonesia Stock Exchange in 2018-2021. This study used a sample of 22 companies during the 2018-2021 period using purposive sampling. This study uses secondary data with descriptive statistical data analysis methods, classical assumption test, and hypothesis testing. The results of this study indicate that the extent of voluntary disclosure has a positive effect on the cost of equity capital with a significant value of 0.006. Meanwhile, information asymmetry, earnings quality, and firm size have no significant effect on the cost of equity capital.